Technical Note on Synchronized Approval of Flexible Credit Lines for Multiple Countries. (Policy Papers; Policy Paper ;, 2010)
As foreshadowed in the Executive Board Report to the IMFC on the Fund's Mandate, this technical note sketches the procedures under which synchronized approval of Flexible Credit Line (FCL) arrangements for multiple member countries could be undertaken under the existing FCL Decision and other Fund policies.1 When multiple members face the same shock, synchronized approval of FCL arrangements could strengthen the effectiveness of the response to the common shock and minimize first-mover problems. This technical note neither modifies existing Fund policies, nor establishes a new financing instrument.